Effect of cenospheres on the engineering properties of lightweight cementitious composites: A comprehensive review. (15th May 2022) - Danish, Aamar; Mosaberpanah, Mohammad Ali; Tuladhar, Rabin; Salim, Muhammad Usama; Yaqub, Muhammad Arslan; Ahmad, Naveed
Abstract: The increased demand for cementitious materials due to rapid industrialization and urbanization has raised several environmental concerns. To construct environmentally sustainable infrastructure, the possibility of using industrial waste (like cenospheres) as construction materials is highly desirable with various economical and practical advantages. Recent studies revealed the practicality of using cenospheres as lightweight material to prepare structural lightweight cementitious materials. Therefore, this article discusses the properties of cenospheres related to the construction sector. Moreover, the effect of cenospheres on the engineering properties (i.e., physical, rheological, mechanical, durability properties), and sustainable benefits of cenosphere modified cementitious materials are comprehensively documented. The article concludes that cenosphere-incorporated cementitious materials can attain significant improvement in the domain of lower density, rheological properties, thermal conductivity, acoustic insulation, and sustainability development, etc. It can also be concluded that cenosphere can replace approximately 10% and 30% of cement and fine aggregates, respectively without causing any significant detrimental impact on the engineering properties of cementitious composites. Highlights: Overview of the properties of cenospheres are documented. Physical, rheological and microstructural properties of cenosphere-modified LWCC are explained. Mechanical, structural, and durability properties of cenosphere-modified LWCC are discussed. Sustainability benefits of cenosphere-modified LWCC are highlighted.